Coronary Artery Disease Diagnosis Based on Electrocardiogram Signal Analysis - Nguyen, Thi Thanh Van; Chí, Trần Như; Chiều, Lê Văn (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 3, 2017)
An electrocardiogram (ECG) records and displays electrical impulses during cardiac activity. Studying the features of ECG signals to detect cardiac abnormalities is important in the medical field. This report presents a method for the detection of coronary artery diseases, i.e., Atrial Enlargement and Ventricular Enlargement, based on the analysis of ECG signals associated with standard indicators. A program performing ECG analysis for the detection of ventricular thickening and atrial thickening syndrome has been developed and verified with recorded ECG signal. The obtained results show a high accuracy diagnostic results, promising the ability to integrate the program into the ECG measuring equipment for screening and autonomus diagnosis.